2018
DOI: 10.3758/s13428-018-1142-4
|View full text |Cite
|
Sign up to set email alerts
|

The Tool for the Automatic Analysis of Cohesion 2.0: Integrating semantic similarity and text overlap

Abstract: This article introduces the second version of the Tool for the Automatic Analysis of Cohesion (TAACO 2.0). Like its predecessor, TAACO 2.0 is a freely available text analysis tool that works on the Windows, Mac, and Linux operating systems; is housed on a user's hard drive; is easy to use; and allows for batch processing of text files. TAACO 2.0 includes all the original indices reported for TAACO 1.0, but it adds a number of new indices related to local and global cohesion at the semantic level, reported by l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
71
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(78 citation statements)
references
References 57 publications
3
71
0
4
Order By: Relevance
“…In similar findings to those of the current study, Crossley et al. () reported that advanced speakers used a number of key‐phrases (i.e., four‐word sequences from the source text) in their speech, and that expert raters judged such speech samples to be proficient.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In similar findings to those of the current study, Crossley et al. () reported that advanced speakers used a number of key‐phrases (i.e., four‐word sequences from the source text) in their speech, and that expert raters judged such speech samples to be proficient.…”
Section: Discussionsupporting
confidence: 87%
“…First, the results underlined the important influence of task instructions on use of task‐specific MWSs, supporting the well‐documented learner behavior of text mining (i.e., transferring MWSs from input texts to L2 output; Boers et al., ; Hoang & Boers, ). The observed tendency of advanced speakers to use a great number of task‐specific expressions accords with previous research exploring cohesion (or keyword and key‐phrase overlap) between the task prompt and the speaker response and its impact on expert ratings of oral proficiency in the TOEFL‐iBT integrated tasks (Crossley, Kyle, & Dascalu, ). In similar findings to those of the current study, Crossley et al.…”
Section: Discussionsupporting
confidence: 87%
“…These indices tap into the extent to which characteristic words and n-grams from the source text are used in the speech transcript. TAACO 2.0 identifies single-and multi-word keywords using the news and magazine sections of the Corpus of Contemporary American English (COCA) as a reference corpus (for a detailed description, see Crossley et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…To investigate the validity of Coh-Viz, we benchmarked the three structural indicators obtained by CohViz to convergent and divergent measures of text cohesion commonly used in well-established assessment systems for writing quality [36,46]. Convergent validity can be assessed by comparing the fragments as the central measure of text cohesion in CohViz to other text cohesion measures (e.g., argument overlap, LSA-dependent cohesion measures) [39]. Divergent validity can be assessed by comparing CohViz to divergent measures of text cohesion (e.g., syntactic or lexical complexity as indicators of writing quality).…”
Section: Methodsmentioning
confidence: 99%
“…Regarding the validity of CohViz, we assessed the convergent and divergent validity of the CohViz system with automated measures from well-established assessment systems [36][37][38][39], as used for example by the well-known system Coh-Metrix [40]. As CohViz was predominantly designed to provide feedback on the cohesion of students' writing, we focused on the number of fragments as the central indicator of cohesion provided by CohViz and compared it with convergent (i.e., argument overlap, semantic overlap) and divergent (i.e., syntactic complexity, lexical diversity, and word concreteness) linguistic features of text cohesion.…”
Section: Overview Of the Current Studymentioning
confidence: 99%